2022
DOI: 10.1177/0272684x221094151
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Medications Among People Living With HIV in the Era of COVID-19 in Central Ethiopia and Perceived Impact of the Pandemic

Abstract: Aim: This study assessed the level of adherence to antiretroviral drugs and the associated factors among clients who have a follow-up at public health facilities in central Ethiopia. Method: A multi-site cross-sectional study was conducted from August 1–30, 2020 at seven public health institutions. A systematic random sampling method was used to recruit 385 participants. Data was collected using a structured interviewer-administered questionnaire. Analysis was done using descriptive statistics, and binary logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…West et al found that at the beginning of the pandemic, access to clinics was hampered due to transport limitations, which raised concerns about shortages of ART and increased anxiety [ 25 ]. Two studies published in 2023 highlighted interruptions in ART adherence attributed to the depletion of ART inventory [ 22 ] and unavailability of medications [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…West et al found that at the beginning of the pandemic, access to clinics was hampered due to transport limitations, which raised concerns about shortages of ART and increased anxiety [ 25 ]. Two studies published in 2023 highlighted interruptions in ART adherence attributed to the depletion of ART inventory [ 22 ] and unavailability of medications [ 32 ].…”
Section: Resultsmentioning
confidence: 99%